Social media marketing all-in-one for dummies - Zimmerman, Jan; Ng, Deborah (--For dummies., 2015)
BOOKS 9 IN 1 The Social Media Mix Cybersocial Tools Content Marketing Twitter® Facebook® and Instagram™ LinkedIn® Pinterest™ Other Social Media Marketing Sites Measuring Results; Building on Success A new and improved edition of the bestselling social media marketing book Marketing your business through social media isn't an option these days-it's imperative. Inside this bestselling guide, you'll find out how to apply the marketing savvy you already have to the social media your prospects are using, helping you reach and keep more customers, make more sales, and boost your bottom line. M.